Broken Relationships: Derisking by Correspondent Banks and International Trade - Borchert, Lea; De Haas, Ralph; Kirschenmann, Karolin; Schultz, Alison (Review of Financial Studies, 2026)
We study how terminated correspondent banking relationships affect international trade. Drawing on firm-level export data from emerging Europe, we show that when local banks lose access to correspondent services, their corporate clients, especially small- and medium-sized enterprises, experience significant export declines. Firms only partially offset lost exports with higher domestic sales, resulting in lower total revenues and employment. Other firms cease operations entirely. These firm-level impacts aggregate to lower product-level exports from countries more exposed to correspondent bank retrenchment.